X-Ray Interaction Mechanisms in Medical Imaging: A Critical Exploration - Aldughayyim, Waleed Saud S; Alqahtani , Siraj Gharaeeb; Alosaimi, Abdulmohsen Mohammed M; Alotaibi, Saad Abdullah M; Alohali , Waleed Abdullah; Aloraini , Mohammed Abdulaziz M; Al-Mutairi, Ghalia Suwaileh; Alanazi, Meshal Rohil (Journal of Ecohumanism, 2024)
X-ray interactions with matter are fundamental to the success of medical imaging, influencing image quality, diagnostic accuracy, and patient safety. This study critically explores the primary interaction mechanisms—photoelectric absorption, Compton scattering, and coherent scattering—and their implications in various medical imaging modalities. By analyzing their effects on image resolution, contrast, and radiation dose, the study highlights the strengths and limitations of each interaction mechanism. The findings underscore the role of photoelectric absorption in high-contrast imaging, the challenges posed by Compton scattering in reducing noise, and the minimal clinical significance of coherent scattering. Emphasis is placed on optimizing imaging parameters and adopting advanced technologies such as dual-energy CT and AI-enhanced imaging to balance diagnostic efficacy with radiation safety. This exploration provides valuable insights into the interplay of X-ray physics and medical imaging, paving the way for enhanced diagnostic practices and future innovations.